Probiótico e ácidos orgânicos na alimentação inicial de frangos de corte: Desempenho zootécnico, morfometria e microbiologia intestinal - Barbieri, Adriano [UNESP] (2015)
There are few researches in which probiotics and organic acids are tested synergistically. To this end, we conducted an experiment using 900 broiler chicks males of Cobb, distributed in a completely randomized design in a factorial 2x2 + 1 (supplemented or not with probiotic), (supplemented or not with organic acids) and (basal diet with antibiotic and anticoccidial inclusion). The broilers were challenged with Eimeria acervulina, E. maxima and E. tenella. The performance data were evaluated at periods of 1-7, 1-10, 1-14, 1-21 and 1-42 days, and the antibiotic was efficient in almost every phase. The effects of probiotic and organic acids in the performance were inconclusive and the same happened for the evaluated morphometric characteristics. It was hardly noticed the synergic effect expected by the interaction between the probiotic and organic acids. The probiotic increased the count of anaerobic bacteria in the small intestine after 14 days while the antibiotic reduced the count in the same period. The relative weight and the length of the small intestine were lower in the presence of the antibiotic at 21 days, as well as the morphometric characteristics evaluated in the same age also decreased. However, at the 42° day the effect on the relative size, length and morphology of the intestine did not differ for any of the tested additives. In front of imposed experimental challenge, probiotic and organic acids shown to be inefficient as it concerns the replacement of antibiotics as performance enhancers